Effects of continuous positive airway pressure on lung mechanics of babies after operation for congenital heart disease. Issue 10 (October 1975) - Cogswell, J J; Hatch, D J; Kerr, A A; Taylor, B
Abstract : The effect of continuous positive airway pressure (CPAP) on lung mechanics was investigated in 12 babies after operation for severe congenital heart disease. At the time of study all babies were receiving or being weaned from ventilatory support and had abnormally low lung volume or compliance. During CPAP there was a fall in the pulmonary resistance which, with a slight decrease in minute ventilation, resulted in a significant decrease in the work of breathing. It is suggested that lowering the oxygen cost of breathing may contribute to the improvement in arterial oxygenation seen when CPAP is used.